Advanced Glycated apoA-IV Loses Its Ability to Prevent the LPS-Induced Reduction in Cholesterol Efflux-Related Gene Expression in Macrophages - Ligia Shimabukuro Okuda; Rodrigo Tallada Iborra; Paula Ramos Pinto; Ubiratan Fabres Machado; Maria Lucia Corrêa-Giannella; Russell Pickford; Tom Woods; Margaret Anne Brimble; Kerry-Anne Rye; Marisa Passarelli (Mediators of Inflammation)
We addressed how advanced glycation (AGE) affects the ability of apoA-IV to impair inflammation and restore the expression of genes involved in cholesterol efflux in lipopolysaccharide- (LPS-) treated macrophages. Recombinant human apoA-IV was nonenzymatically glycated by incubation with glycolaldehyde (GAD), incubated with cholesterol-loaded bone marrow-derived macrophages (BMDMs), and then stimulated with LPS prior to measurement of proinflammatory cytokines by ELISA. Genes involved in cholesterol efflux were quantified by RT-qPCR, and cholesterol efflux was measured by liquid scintillation counting. Carboxymethyllysine (CML) and pyrraline (PYR) levels, determined by Liquid Chromatography-Mass Spectrometry (LC-MS/MS), were greater in AGE-modified apoA-IV (AGE-apoA-IV) compared to unmodified-apoA-IV. AGE-apoA-IV inhibited expression of interleukin 6 (Il6), TNF-alpha (Tnf), IL-1 beta (Il1b), toll-like receptor 4 (Tlr4), tumor necrosis factor receptor-associated factor 6 (Traf6), Janus kinase 2/signal transducer and activator of transcription 3 (Jak2/Stat3), nuclear factor kappa B (Nfkb), and AGE receptor 1 (Ddost) as well as IL-6 and TNF-alpha secretion. AGE-apoA-IV alone did not change cholesterol efflux or ABCA-1 levels but was unable to restore the LPS-induced reduction in expression of Abca1 and Abcg1. AGE-apoA-IV inhibited inflammation but lost its ability to counteract the LPS-induced changes in expression of genes involved in macrophage cholesterol efflux that may contribute to atherosclerosis.